2005
DOI: 10.1542/peds.2004-0211
|View full text |Cite
|
Sign up to set email alerts
|

Is Noncompliance Among Adolescent Renal Transplant Recipients Inevitable?

Abstract: The absence of cases of noncompliance in adolescents who underwent commercial living unrelated kidney transplantation suggests that although noncompliance is prevalent, it is not inevitable. Strategies to decrease noncompliance in young patients with chronic illnesses can be learned from the experience with transplant recipients. The general pediatrician has a central role in identifying and addressing the problem of noncompliance in adolescents with chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 25 publications
4
72
1
3
Order By: Relevance
“…The general fi ndings from these articles showed that patients who had emotional support and help from family members, friends or healthcare providers were more likely to be compliant to the treatment (Stanton 1987;Lorenc and Branthwaite 1993;Garay-Sevilla et al 1995;Milas et al 1995;Kyngas 1999;Okuno et al 1999;Stromberg et al 1999;Kyngas 2001;Kyngas and Rissanen 2001;Thomas et al 2001;Loffl er et al Factors affecting compliance 2003;DiMatteo 2004;Feinstein et al 2005;Seo and Min 2005;Voils et al 2005). The social support helps patients in reducing negative attitudes to treatment, having motivation and remembering to implement the treatment as well.…”
Section: Social Supportmentioning
confidence: 99%
“…The general fi ndings from these articles showed that patients who had emotional support and help from family members, friends or healthcare providers were more likely to be compliant to the treatment (Stanton 1987;Lorenc and Branthwaite 1993;Garay-Sevilla et al 1995;Milas et al 1995;Kyngas 1999;Okuno et al 1999;Stromberg et al 1999;Kyngas 2001;Kyngas and Rissanen 2001;Thomas et al 2001;Loffl er et al Factors affecting compliance 2003;DiMatteo 2004;Feinstein et al 2005;Seo and Min 2005;Voils et al 2005). The social support helps patients in reducing negative attitudes to treatment, having motivation and remembering to implement the treatment as well.…”
Section: Social Supportmentioning
confidence: 99%
“…clinicians/transplant centers evaluated this relationship (12,13 (3,5,7,8,10), with some exceptions to this trend (2,11 (14,21,24,32,33). (3,(5)(6)(7)(8)(9)(10)(11)(34)(35)(36).…”
Section: Immunosuppressant Therapy Adherencementioning
confidence: 99%
“…(3,(5)(6)(7)(8)(9)(10)(11)(34)(35)(36). Therefore, the belief that adolescents are more nonadherent compared to children should be further examined.…”
Section: Immunosuppressant Therapy Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…Conocer el comportamiento de nuestros pacientes con respecto a la medicación prescrita es de vital importancia, tanto para evitar errores en las dosis que conlleven mayor riesgo de efectos secundarios como para optimizar los resultados de la medicación. En un estudio de Feinstein encuentran una elevada prevalencia de incumplimiento en adolescentes que se administran solos las medicación 5 . También se ha descrito una adherencia signifi cativamente mejor en los pacientes que tienen mayor conocimiento del régimen terapéutico, que sus padres o cuidadores son responsables del tratamiento y los que usan pastilleros unidosis para organizar la medicación 6 .…”
unclassified